Pengaruh Proactive Personality Dan Pemberdayaan Psikologis Terhadap Perilaku Inovatif Melalui Creative Self Efficacy - Irfan Helmy; Marynta Putri Pratama (Universitas Amikom Purwokerto, 2018)
The purpose of this study was to examine the effect of proactive personality and psychological empowerment on innovative behavior with creative self efficacy (CSE) as a mediating variable. This research was carried out in elementary schools with a total of 150 teachers. This study uses a quantitative approach with a path analysis statistical test tool. The results showed that proactive personality, psychological empowerment and CSE influence innovative behavior. In addition CSE has been proven to mediate the relationship between proactive personality and psychological empowerment of innovative behavior.